Autonomic disbalance their relationship with the cardiovascular hiperreactivity, the resistance to the insulin and the high blood pressure. - Mikhail Benet Rodríguez; Juan José Apollinaire Pennini; Milagros L León Regal; Yosvel Curbelo Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
During many years has been debated the paper of the Autonomous Nervous System in the development of the arterial hypertension, in passing it constitutes one of the important theories that physiologists. Recently some authors have involved the activity of that system with the resistance to the insulin and with other important aspects that influence in the appearance of arterial hypertension. The objective of this work is to contribute new theoretical elements that link the changes of the activity of the Autonomous Nervous System with the presence of cardiovascular hipereactivity and sustained arterial hypertension.